Exercise for prevention of falls and fall-related injuries in neurodegenerative diseases and aging-related risk conditions: a meta-analysis - Feng, Feifei; Xu, Haocheng; Sun, Yu; Zhang, Xin; Li, Nan; Sun, Xun; Tian, Xin; Zhao, Renqing (Frontiers in Endocrinology, 2023)
Neurodegenerative diseases often cause motor and cognitive deterioration that leads to postural instability and motor impairment, while ageing-associated frailty frequently results in reduced muscle mass, balance and mobility. These conditions increase the risk of falls and injuries in these populations. This study aimed to determine the effects of exercise on falls and consequent injuries among individuals with neurodegenerative diseases and frail ageing people. Electronic database searches were conducted in PubMed, Cochrane Library, SportDiscus, and Web of Science up to Jan 1, 2023. Randomised controlled trials that reported the effects of exercise on falls and fall-related injuries in neurodegenerative disease and frail ageing people were eligible for inclusion. The intervention effects for falls, fractures, and injuries were evaluated by calculating the rate ratio (RaR) or risk ratio (RR) with 95% confidence interval (CI). Sixty-four studies with 13241 participants met the inclusion criteria. Exercise is effective in reducing falls for frail ageing people (RaR 0.75, 95%CI 0.68-0.82) and participants with ND (0.53, 0.43-0.65) [Dementia (0.64, 0.51-0.82), Parkinson's Disease (0.49, 0.39-0.69), and stroke survivors (0.40, 0.27-0.57)]. Exercise also reduced fall-related injuries in ND patients (RR 0.66, 95%CI 0.48-0.90), and decreased fractures (0.63, 0.41-0.95) and fall-related injuries (0.89, 0.84-0.95) among frail ageing people. For fall prevention, balance and combined exercise protocols are both effective, and either short-, moderate-, or long-term intervention duration is beneficial. More importantly, exercise only induced a very low injury rate per participant year (0.007%, 95%CI 0-0.016) and show relatively good compliance with exercise (74.8, 95% CI 69.7%-79.9%). Exercise is effective in reducing neurodegenerative disease-and ageing-associated falls and consequent injuries, suggesting exercise is an effective and feasible strategy for the prevention of falls.